Case Report: PROS1 (p.Leu584Arg) pathogenic mutation causes portal and superior mesenteric venous thromboembolism - Ding, Peng; Zhou, Yuan; Zhang, Kai-Chen; Li, Sheng; Long, Kun-lan; Chen, Jun; Chen, Ying-jie; Gao, Pei-yang (Frontiers in Cardiovascular Medicine, 2023)
Background Genetic and acquired risk factors are fundamental to developing venous thromboembolism. Autosomal dominant protein S deficiency caused by pathogenic mutations in the PROS1 gene is a well-known risk factor for thrombophilia. Case presentation We report a 30-year-old male patient who presented to the hospital with portal vein thrombosis. The patient had a history of abdominal pain for one month. Abdominal vascular CT showed venous thrombosis in the portal vein and superior mesenteric vein. He was diagnosed with “portal and superior mesenteric vein thrombosis, small bowel obstruction and necrosis, acute upper gastrointestinal bleeding (UGIB), hemorrhagic shock.” Serum protein S levels were decreased, and gene sequencing revealed a heterozygous missense mutation in PROS1, c.1571T > G (p.Leu584Arg). The patient received anticoagulation therapy with Enoxaparin Sodium and rivaroxaban, transjugular intrahepatic portosystemic shunt (TIPS), and ICU treatments. Although the patient had a severe bleeding event during anticoagulation therapy, he recovered well after active treatment and dynamic monitoring of anti-Xa. Conclusion Hereditary protein S deficiency caused by a mutation in the PROS1 gene is the genetic basis of this patient, and Enoxaparin Sodium and rivaroxaban have been shown to be highly effective.